1996
DOI: 10.4012/dmj.15.226
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Skin Irritation and Sensitization of Two Diol Solutions used as Experimental Dentin Primers in Humans and Guinea Pigs

Abstract: The purpose of the present study was to evaluate the safety of ethylene glycol (EG) and 1, 6-hexanediol (HD) solutions as experimental dentin primers when subjected to the guinea pig maximization test (GPMT), primary irritation test, cumulative skin irritation test and human patch test. No primary and cumulative skin irritation resulting from the use of 62.5% EG or 45% HD solutions was observed. In the case of GPMT, the animals sensitized with 2-hydroxyethyl methacrylate (2-HEMA) responded to 100% HD. 62.5% EG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…It is widely known that repeated handling of 2-HEMA causes contact dermatitis on the fingertips of dental clinicians as a result of a delayed allergic reaction (Kanerva et al, 1994;Katsuno et al, 1995Katsuno et al, , 1996Katsuno et al, , 1998Kurihara et al, 1996). Yamada et al (1989) and Horiguchi et al (1995) reported that various bonding agents produce a white substance on the oral mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely known that repeated handling of 2-HEMA causes contact dermatitis on the fingertips of dental clinicians as a result of a delayed allergic reaction (Kanerva et al, 1994;Katsuno et al, 1995Katsuno et al, , 1996Katsuno et al, , 1998Kurihara et al, 1996). Yamada et al (1989) and Horiguchi et al (1995) reported that various bonding agents produce a white substance on the oral mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Information from case reports for the alkane diols included allergic contact dermatitis as a result of dermal exposure to 1,5-Pentanediol (.5 to 10%) in various creams, 104,105 a recommendation by study researchers for dental professionals exposed to Hexanediol in dentin primers to take precautions because of the potential to cause contact dermatitis following repeated occupational exposure, 97 and adverse effects reported in adults (including death) and poisoning in children from oral exposure to 1,4-Butanediol (varying doses). 13,22,[106][107][108]…”
Section: Case Reportsmentioning
confidence: 99%
“…Skin irritation testing of Propanediol, 1,4-Butanediol, 2,3-Butanediol, 1,5-Pentanediol, Hexanediol, 1,10-Decanediol, Methylpropanediol, Butyl Ethyl Propanediol, and Isopentyldiol was conducted. Results indicated the following observations: Propanediol (undiluted) was mildly irritating to rabbit skin in 24-hour occlusive patch tests 12 ; 1,4-Butanediol (undiluted) caused only minimal redness after application to rabbit ears and no irritation was observed in a 24-hour occlusive patch test on intact and abraded rabbit skin; 82 2,3-Butanediol (undiluted) was non-irritating to rabbit skin in a 24-hour occlusive patch test; 16 1,5-Pentanediol (undiluted) was non-irritating to rabbit skin in both a 24-hour non-occlusive skin test 79 and a 20-hour occlusive patch test on intact and scarified skin; 14 Hexanediol (45 to 80%) was non-irritating to animal skin in both non-occlusive and occlusive tests performed with approximately 24-hour dermal exposure; 15,79,80,97 1,10-Decanediol (1.2% in a trade name mixture also containing an unspecified amount of Propylene Glycol) was non-irritating to rabbit skin in a 24 h occlusive patch test; 84 Methylpropanediol (undiluted) was non-irritating to animal skin; 20 Butyl Ethyl Propanediol (undiluted) was non-to-minimally irritating to rabbit skin in 4-hour semi-occlusive patch tests; 2,17 Isopentyldiol (undiluted) was non-to-slightly irritating to rabbit skin in 24-hour occlusive and semi-occlusive patch tests.…”
Section: Dermal Irritation and Sensitization Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same vein, Pegum and Medhurst reported that an acrylic monomer could permeate latex gloves 5) , while Katsuno et al warned that dental healthcare workers should use primers with care [6][7][8][9][10] . In 1989, Chigira et al reported that glyceryl mono-methacrylate (GM) exhibited a better priming effect than 2-HEMA 11) .…”
Section: Introductionmentioning
confidence: 99%